The Expanding Role of Mitral Valve Repair in Triple Valve Operations: Contemporary North American Outcomes in 8,021 Patients - Suri, Rakesh M. (Ann Thorac Surg, 2014)
BACKGROUND: Although the operative risk of multivalve operations has historically been high, current outcomes are poorly understood. We sought to evaluate factors influencing contemporary results of triple-valve operations using The Society of Thoracic Surgeons Adult Cardiac Surgery Database. METHODS: Among patients undergoing combined mitral, aortic, and tricuspid valve (triple- valve) operations between 1993 and 2011, aortic valve repair patients were excluded and those having aortic valve replacement were analyzed according to whether they underwent repair vs replacement of the mitral valve (MV) and tricuspid valve (TV). Temporal trends in operative death and clinical outcomes were examined using unadjusted and adjusted analyses. RESULTS: A total of 8,021 triple-valve patients were studied. The median (25(th) percentile, 75(th) percentile) age was 67 years (59, 77 years), 4,809 (60%) were women, 4,488 (56%) had New York Heart Association class III to IV symptoms, and the mean (25(th) percentile, 75(th) percentile) ejection fraction was 50% (40%, 60%). MV repair was performed in 2,728 (34%) patients overall and increased over time from 13% (1993 to 1997) to 41% (2008 to 2011). TV repair was performed in 7,512 (94%) patients overall and increased over time from 86% (1993 to 1997) to 96% (2008 to 2011). Unadjusted operative mortality decreased from 17% in 1993 to 9% in 2011. Adjusted odds ratios (95% confidence intervals) of operative mortality were lower in those having MV repair (0.72 [0.61 to 0.85]), TV repair (0.64 [0.50 to 0.83]), and MV D TV repair (0.46 [0.34 to 0.63]) compared with those having replacements. Unadjusted and adjusted odds of stroke were similar between groups and not significant for all. CONCLUSIONS: This large series demonstrates that surgical results of triple-valve operations have continued to improve during the past 18 years. MV and TV repair were associated with improvements in early survival. Although further study is required to understand late outcomes, these data suggest that broader efforts to perform MV repair instead of replacement in this high-risk patient population appear warranted.